Resource overheads and attainable rates for trapped-ion lattice surgery - Hudson Leone; Thinh Le; S. Srikara; Simon Devitt (Physical Review Research)
We present estimates for the number of ions needed to implement fault-tolerant lattice surgery between spatially separated trapped-ion surface codes. Additionally, we determine attainable lattice surgery rates given a number of dedicated “communication ions” per logical qubit. Because our analysis depends heavily on the rate that syndrome extraction cycles take place, we survey the state-of the art and propose three possible cycle times between 10 and 1000µs that we could reasonably see realized provided certain technological milestones are met. Consequently, our numerical results indicate that hundreds of resource ions will be needed for lattice surgery in the slowest case, while close to a hundred thousand will be needed in the fastest case. The main factor contributing to these prohibitive estimates is the limited rate that ions can be coupled across traps. Our results indicate an urgent need for optical coupling to improve by one or more orders of magnitude for trapped-ion quantum computers to scale.